Isolation and Characterization of Lactic Acid Bacteria from Inasua - Ferymon Mahulette; Nisa Rachmania Mubarik; Antonius Suwanto; Widanarni Widanarni (Universitas Gadjah Mada, 2016)
Inasua is a traditionally product of wet salt fish fermentation produced by Teon, Nila and Serua (TNS) Communities in Central Maluku, Indonesia. The community made this fermented fish to anticipate the lean time when fisherman could not go to sea. The fish that used as inasua raw material is demersal fishes that live around coral reefs, such as Samandar fish (Siganatus guttatus), Gala-gala fish (Lutjanus sp.) and Sikuda fish (Lethrinus ornatus). The objective of the research was to isolate and characterize of bacterial indigenous in Inasua from three producers in Seram Island. The measurement of pH from inasua samples were 5.9, 5.0 and 5.8, respectively. The highest number of lactic acid bacteria was found from Gala – gala inasua was 2,5x107 cfu/g sample. Isolation of all isolates bacteria from inasua showed that a total of 7 isolates of bacteria was obtained from Samadar inasua, 9 isolates from Gala-gala inasua, and 7 isolates from Sikuda inasua. From a total of 23 isolates, only 6 isolates had characteristic as lactic acid bacteria that were Gram positive, negative catalase, and cocci shape. The microscopic characteristics of the isolates are coccid in pairs or uniforms which combine to form tetrads. Carbohydrate utilization test of selected isolate by using API 50 CHB kit indicated that 13 carbohydrates are fermented by these isolates after incubation for 48 hours. The research was concluded that the dominant bacteria in inasua sample is cocci-lactic acid bacteria.Keywords : fermented fish, inasua, lactic acid bacteria, MRSA medium